Gastrointestinal stromal tumors - Soriano-Lorenzo, Jorge (2019)
Gastrointestinal stromal tumors (GIST) are mesenchymal neoplasms that arise in the gastrointestinal tract, usually in the stomach or the small intestine. GISTs can arise at any age, but more than 80% are reported in individuals older than 50 years men and women are affected at a roughly similar frequency. The few patients are who younger frequently have GIST associated with a syndrome. The clinical manifestations are non-specifics. The computer-tomography is recommended for staging and follow-up. The KIT and DOG1 are the most sensitive and specific immunohistochemistry markers. The standard treatment of localized GIST is complete surgical excision of the lesion, with or without adjuvant imatinib in dependence with the relapse risk. Neoadjuvant imatinib is the standard treatment for locally advanced and metastatic disease. In locally advanced and metastatic disease the imatinib treatment should be continued indefinitely. Following confirmed progression, or intolerance, to imatinib the standard second-line treatment is sunitinib.